Navigating Multilingual Classrooms: Teachers’ Perspectives and Practices of Translanguaging in Ghanaian Junior High School. - Lawer, Richard Ayertey (Fakultas Ilmu Budaya, Universitas Mulawarman, 2025)
This study investigated teachers’ practice and perceptions of translanguaging in junior high school classrooms in Ghana, focusing on how teachers negotiate language use. In this study, the awareness, understanding, and application of translanguaging by teachers were explored through qualitative interviews. The results show that although most participants were unfamiliar with the term ‘‘translanguaging,’’ the practice is a common strategy to enhance students’ comprehension and participation in classrooms. Teachers use translanguaging as a pedagogical approach to fill in linguistic gaps and to support plurilingual students. In contrast to the language policy that makes English the sole medium of instruction at the junior high school level, Ghanaian teachers in some public junior high schools continue practicing translanguaging, mostly through tacit approval of their circuit supervisors and school heads. The findings underline the need for rethinking language policies to reflect the realities of bilingual classrooms and recommend that intentionally incorporating translanguaging into formal educational frameworks at the junior high level could foster more inclusive and effective teaching and learning in the classrooms. This research contributes to extant literature advocating for the recognition and legitimisation of translanguaging in multilingual educational contexts, emphasising its role in improving teaching and learning outcomes in Ghanaian classrooms.